Craniofacial Morphology, Head Posture and Hyoid Bone Position - Ezgi Atik; İlken Kocadereli (Galenos Yayinevi, 2011)
Head and neck region has recently been an investigation topic in orthodontics because of the effects of the dentofacial structures. In this respect, the relation between head posture, craniofacial morphology and hyoid bone will be mentioned in the present review.